A function for binaural integration in auditory grouping and segregation in the inferior colliculus - Nakamoto, Kyle T. (J Neurophysiol, 2014)
Responses of neurons to binaural, harmonic complex stimuli in urethane-anesthetized guinea pig inferior colliculus (IC) are reported. To assess the binaural integration of harmonicity cues for sound segregation and grouping, responses were measured to harmonic complexes with different fundamental frequencies presented to each ear. Simultaneously gated harmonic stimuli with fundamental frequencies of 125 Hz and 145 Hz were presented to the left and right ears, respectively, and recordings made from 96 neurons with characteristic frequencies >2 kHz in the central nucleus of the IC. Of these units, 70 responded continuously throughout the stimulus and were excited by the stimulus at the contralateral ear. The stimulus at the ipsilateral ear excited (EE: 14%; 10/70), inhibited (EI: 33%; 23/70), or had no significant effect (EO: 53%; 37/70), defined by the effect on firing rate. The neurons phase locked to the temporal envelope at each ear to varying degrees depending on signal level. Many of the cells (predominantly EO) were dominated by the response to the contralateral stimulus. Another group (predominantly EI) synchronized to the contralateral stimulus and were suppressed by the ipsilateral stimulus in a phasic manner. A third group synchronized to the stimuli at both ears (predominantly EE). Finally, a group only responded when the waveform peaks from each ear coincided. We conclude that these groups of neurons represent different “streams” of information but exhibit modifications of the response rather than encoding a feature of the stimulus, like pitch.